2015
DOI: 10.1007/s00436-015-4603-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymerase chain reaction on cerebrospinal fluid for diagnosis of cerebral coenurosis in small ruminants

Abstract: Sheep and goats serve as intermediate hosts for the canine tapeworm Taenia multiceps. The cysts produced by the intermediate stage of parasite are usually found in the cerebral hemispheres of small ruminants, and the resulting disease is commonly known as coenurosis. Coenurosis is clinically manifested in the form of various nervous symptoms, depending on the exact location of the cyst. The variety of neurological symptoms contributes to the complexity of clinical diagnosis and reinforces the need for a more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Oryan et al [19] demonstrated that the DNA of T. multiceps presents in the cerebrospinal fluid (CSF) of sheep and goats with this disease, and this can be diagnosed by amplification of the cox1 gene. This method suggested that PCR can be used to amplify parasite DNA from the CSF and is valuable for the accurate identification of coenurosis cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oryan et al [19] demonstrated that the DNA of T. multiceps presents in the cerebrospinal fluid (CSF) of sheep and goats with this disease, and this can be diagnosed by amplification of the cox1 gene. This method suggested that PCR can be used to amplify parasite DNA from the CSF and is valuable for the accurate identification of coenurosis cases.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical manifestations increase the complexity of diagnosis. Thus, it is urgently necessary to develop a diagnostic approach which is both specific and practically acceptable [19]. In many areas, the prevalence of cerebral coenurosis is believed to be underestimated because of the lack of reliable diagnostic methods [20].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors were reported presence of cysts in different locations of goat's body; a cyst was found over the right mandible (Devasana et al, 1998), muscles of the thighs ( Jyothimol and Sangaran, 2015), hips and shoulders (Ramadan et al, 1973), neck region, in connective tissue near the splenic ligament and in intercostals and abdominal musculature (Shastri et al, 1985). It was also reported in visceral cavity including heart, diaphragm, thoracic cavity, abdominal cavity and pelvic inlet, pericardium and myocardium (ICAR, 2016-17), and in intramuscular and subcutaneous tissues of goats (Oryan et al, 2014). Shivapraksh and Reddy (2009) also found multiple subcutaneous coenuri in neck, prescapular region, abdomen and limbs in a herd of goats as C.gaigeri because of their extra-cranial locations.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 91%
“…Hence, more specific and reliable diagnostic tools are required. However, in humans, diagnosis is based on the identification of cysts in the brain by magnetic resonance imaging (MRI) and computerized tomography (CT) scan 38 . When clinical signs of coenurosis were appeared, the prognosis of the disease is extremely poor and fatality rate may reach to 100%.…”
Section: Introductionmentioning
confidence: 99%